A Systematic Literature Review of the Epidemiology, Health-Related Quality of Life Impact, and Economic Burden of Immunoglobulin A Nephropathy - Christina Soeun Kwon; Patrick Daniele; Anna Forsythe; Christopher Ngai (Journal of Health Economics and Outcomes Research)
**Introduction:** This systematic literature review analyzed published evidence on IgA nephropathy (IgAN), focusing on US epidemiology, health-related quality of life (HRQoL), and economic burden of illness.